A Novel Class of Gibberellin 2-Oxidases Control Semidwarfism, Tillering, and Root Development in Rice - Lo, Shuen-Fang (American Society of Plant Biologists, 2008)
Gibberellin 2-oxidases (GA2oxs) regulate plant growth by inactivating endogenous bioactive gibberellins (GAs). Two classes of GA2oxs inactivate GAs through 2β-hydroxylation: a larger class of C(19) GA2oxs and a smaller class of C(20) GA2oxs. In this study, we show that members of the rice (Oryza sativa) GA2ox family are differentially regulated and act in concert or individually to control GA levels during flowering, tillering, and seed germination. Using mutant and transgenic analysis, C(20) GA2oxs were shown to play pleiotropic roles regulating rice growth and architecture. In particular, rice overexpressing these GA2oxs exhibited early and increased tillering and adventitious root growth. GA negatively regulated expression of two transcription factors, O. sativa homeobox 1 and TEOSINTE BRANCHED1, which control meristem initiation and axillary bud outgrowth, respectively, and that in turn inhibited tillering. One of three conserved motifs unique to the C(20) GA2oxs (motif III) was found to be important for activity of these GA2oxs. Moreover, C(20) GA2oxs were found to cause less severe GA-defective phenotypes than C(19) GA2oxs. Our studies demonstrate that improvements in plant architecture, such as semidwarfism, increased root systems and higher tiller numbers, could be induced by overexpression of wild-type or modified C(20) GA2oxs.